2014
DOI: 10.3109/03014460.2014.944216
|View full text |Cite
|
Sign up to set email alerts
|

Lactase genetic polymorphisms and coeliac disease in children: a cohort study

Abstract: There appears to be no significant correlation between C/T -13910 or G/A -22018 SNPs of AtH and CD. Children with C/C or G/G genotype of AtH may not be at greater risk of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Across various studies, HLA-DQ2/DQ8 serotypes have been reported in 13–30% of different populations in India [ 14 ]. The allele prevalence of HLA-DQB1*02 in northern India ranged from 16–31%, while that of HLA-DQB1*0302 ranged from 0–5% which is in accordance with our results [ 7 ]. The significant differences in the frequency of HLA-DQ2 and HLA-DQ8 alleles in Indian (Rajasthan) patients compared with the controls demonstrates the importance of these alleles in CD development, and supports the possibility of using HLA-DQ typing in confirming CD diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Across various studies, HLA-DQ2/DQ8 serotypes have been reported in 13–30% of different populations in India [ 14 ]. The allele prevalence of HLA-DQB1*02 in northern India ranged from 16–31%, while that of HLA-DQB1*0302 ranged from 0–5% which is in accordance with our results [ 7 ]. The significant differences in the frequency of HLA-DQ2 and HLA-DQ8 alleles in Indian (Rajasthan) patients compared with the controls demonstrates the importance of these alleles in CD development, and supports the possibility of using HLA-DQ typing in confirming CD diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Studies from the Western world suggest that 30–35% of the general population express CD-associated HLA genotypes [ 4 5 6 ]. The prevalence of HLA-DQ2 in north Indian populations is around 16–31% while that of DQ8 is around 0–5% [ 7 ]. Over 90% of CD patients express the HLA-DQ2.5 heterodimer (DQA1*05 and DQB1*02).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses for susceptibility genes using whole blood . The majority of studies on autoimmunity within human biology have looked at susceptibility genes for various AIID in multiple populations using DNA extracted from whole blood, amplified via polymerase chain reaction, and genotyped using various methods (see: AlFadhli et al, 2013; AlFadhli & Jahabani, 2014; Ali et al, 2012; Chabchoub et al, 2009; Chua et al, 2010; Diaz‐Horta et al, 2010; Kammoun‐krichen et al, 2008; Kuchay et al, 2015; Makni et al, 2007). Although valuable, data obtained from this type of genetic analysis can tell us about susceptibility to developing autoimmunity, but cannot tell us about current, active AIID or the likelihood that AIID will manifest later in life in individuals with certain genetic variants.…”
Section: What Methods Have Been Used To Measure Autoimmunity In Populmentioning
confidence: 99%
“…Multiple studies in biological anthropology and human biology have found links between AIID susceptibility and a number of gene polymorphisms in multiple populations (Examples: AlFadhli & Jahabani, 2014; AlFadhli, Mohammed, & Shubaili, 2013; Begovich et al, 2004; Bottini et al, 2004; Chabchoub et al, 2009; Chua, Puah, Chew, Tan, & Lian, 2010; Kammoun‐krichen et al, 2008; Kuchay, Thapa, Mahmood, Anwar, & Mahmood, 2015; Kyogoku et al, 2004; Makni, Kacem, Rebaï, Abid, & Ayadi, 2007; Velaga et al, 2004). These polymorphisms and associated AIID include, but are certainly not limited to, the following examples.…”
Section: Why Is Autoimmunity Of Interest To Human Biologists?mentioning
confidence: 99%
“…However, previous data suggest that also patients with CeD on a gluten-free diet frequently claim lactose intolerance and therefore avoid milk and dairy products 2. Recently, it has been demonstrated that there is no association between the type of adult hypolactasia gene mutations and CeD 3. Milk avoidance in patients with CeD may depend on the fact that lactose intolerance is determined not only by the expression of lactase gene but also by the dose of lactose, intestinal flora, gastrointestinal motility, small intestinal bacterial overgrowth and sensitivity of the gastrointestinal tract to the generation of gas and other fermentation products of lactose digestion4 and other unidentified factors.…”
Section: Introductionmentioning
confidence: 99%